2020
DOI: 10.3390/ijms21249382
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Myokines on Reactive Oxygen Species in Ischemia/Reperfusion

Abstract: There is a growing body of evidence showing the importance of physical activity against acute ischemic events in various organs. Ischemia/reperfusion injury (I/R) is characterized by tissue damage as a result of restriction and subsequent restoration of blood supply to an organ. Oxidative stress due to increased reactive oxygen species formation and/or insufficient antioxidant defense is considered to play an important role in I/R. Physical activity not only decreases the general risk factors for ischemia but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 189 publications
(128 reference statements)
0
30
0
Order By: Relevance
“…Reactive oxygen species (ROS) mainly cause the damage of microvessels and parenchymal organs during ischemic tissue reperfusion. The synthesis ability of antioxidant enzymes, which can scavenge free radicals, is impaired in the ischemic tissue, thus aggravating the damage of free radicals to ischemic reperfusion tissue (Neeff et al, 2012;Sun et al, 2014;Szabó et al, 2020). SOD can protect the tissue from ischemia and reperfusion by scavenging free radicals (Ambrosio et al, 1987;Galiñanes et al, 1992;Chen et al, 1996;Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) mainly cause the damage of microvessels and parenchymal organs during ischemic tissue reperfusion. The synthesis ability of antioxidant enzymes, which can scavenge free radicals, is impaired in the ischemic tissue, thus aggravating the damage of free radicals to ischemic reperfusion tissue (Neeff et al, 2012;Sun et al, 2014;Szabó et al, 2020). SOD can protect the tissue from ischemia and reperfusion by scavenging free radicals (Ambrosio et al, 1987;Galiñanes et al, 1992;Chen et al, 1996;Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…46 Reactive oxygen species-mediated apoptosis When blood flow is restored after cerebral ischemia, a large amount of reactive oxygen species (ROS) is produced, which may be one of the causes of neuronal ischemia/reperfusion (I/R) injury. 47 Neuronal cell damage by ROS may occur in association with apoptosis. For example, ROS can damage the plasma membrane, resulting in loss of membrane integrity.…”
Section: Calpain-mediated Apoptosismentioning
confidence: 99%
“…Many studies have shown that inflammation associated with I/R injury can exacerbate myocardial damage [ 96 ], which may cause a condition experimentally similar to IH. On the basis of these studies [ 97 ], we suspected that IH had a direct effect on myokine secretion and conducted the following experiments. We investigated the changes in myokine levels and their regulation mechanisms by IH [ 19 ].…”
Section: Intermittent Hypoxia and Cytokinesmentioning
confidence: 99%